Sistem Rekrutmen dalam Pengembangan Manajemen Sumber Daya Manusia Berdasarkan Konsep Pendidikan Islam - Junaidi, Junaidi; Jamilus, Jamilus (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to explore the implementation of a recruitment system based on the concept of Islamic education in the development of human resource management (HR). The research method used is descriptive qualitative with a case study approach in several organizations that apply Islamic principles in the recruitment process. Data are obtained through interviews, observation, and analysis of related documents. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results showed that the integration of Islamic values in recruitment criteria had a positive impact on work culture, performance, and organizational alignment with Islamic principles. Training employees on Islamic ethics has also proven effective in strengthening their understanding of the values that should be upheld in the work environment. This research provides practical recommendations for organizations in developing an Islamic-based recruitment system, such as integrating Islamic aspects in performance monitoring and evaluation, as well as organizational commitment to human resource development in accordance with Islamic principles.